Thermal conductivity and microstructure characterisation of lightweight alumina and alumina–mullite ceramics. Issue 6 (May 2016) - Zake-Tiluga, Ieva; Svinka, Visvaldis; Svinka, Ruta; Zierath, Bodo; Greil, Peter; Fey, Tobias
Abstract: The thermal conductivity of lightweight alumina and alumina–mullite ceramics produced by slip casting and chemical foaming has been measured as a function of temperature in the range from room temperature to 1100 °C by the laser flash technique. The microstructure of the studied materials was analysed by scanning mercury intrusion porosimetry, electron microscopy, and micro‑computed tomography. Ceramics was fabricated by slip casting. Pores were formed by aluminium reacting with water. Micro-sized SiO2 and plasma-synthesised SiC nanopowder were used as silica sources. The thermal conductivity of the investigated ceramics was in the range from 0.8 to 3.1 W/(m K), depending on the sintering temperature (1650 °C and 1750 °C) and amount of added SiO2 source.